Analisis Bangkitan Perjalanan Penduduk Pada Kompleks Perumahan Taman Sudiang Indah - Dane Cheber Yusmar Tandioga; Rais Rachman; Louise Elizabeth Radjawane (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Taman Sudiang Indah Residence, Biringkanaya Subdistrict, PAI Village is located on the outskirts of Makassar City with a population of ± 2,619 people which will cause travel. Residential generation - trip generation for residents who can be lazy on the road network to the place of activity. This research was conducted to determine household characteristics and household travel characteristics and to model trip generation in Taman Sudiang Indah residence estate.This survey was conducted by filling out a questionnaire in google form. Analyzing the data with descriptive statistical methods of correlation test and multiple linear regression. The results showed that the factors influence trip generation in the Taman Sudiang Indah residence complex were the average family income (X4), the number of working family members (X5), and the number of family members attending school/college (X6) to the number of generation (Y). The trip generation equation model for Taman Sudiang Indah residence is Y = 1.2730 + 0.095 X4 + 0.371 X5 + 0.273 X6, the value of the coefficient of determination (R2) is 25.3% and the value of the correlation coefficient (R) is 50.3%.